2017
DOI: 10.1371/journal.pone.0186729
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphism of the renalase gene is associated with cardiac hypertrophy in female patients with aortic stenosis

Abstract: Renalase decreases circulating catecholamines concentration and is important in maintaining primary cellular metabolism. Renalase acts through the plasma membrane calcium ATPase 4b in the heart, which affects pressure overload but not exercise induced heart hypertrophy. The aim of this study was to test the association between a functional polymorphism Glu37Asp (rs2296545) of the renalase gene and left ventricular hypertrophy in a large cohort of patients with aortic stenosis. The study group consisted of 657 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Some investigators recently also confirmed the association of renalase gene polymorphism with cardiac hypertrophy in female patients with aortic stenosis [31], again suggesting a causal relationship between renalase and cardiac hypertrophy. The authors postulated the potential link knowing that in hypoxia, glycolysis is increased and that renalase is secreted in the manner of preserving primary metabolism [31].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some investigators recently also confirmed the association of renalase gene polymorphism with cardiac hypertrophy in female patients with aortic stenosis [31], again suggesting a causal relationship between renalase and cardiac hypertrophy. The authors postulated the potential link knowing that in hypoxia, glycolysis is increased and that renalase is secreted in the manner of preserving primary metabolism [31].…”
Section: Discussionmentioning
confidence: 81%
“…The most recent genetic testing on the GG genotype of rs2576178 polymorphism concluded that this particular genotype increases renalase levels and thereby contributes to increased risk of coronary artery disease [30]. Some investigators recently also confirmed the association of renalase gene polymorphism with cardiac hypertrophy in female patients with aortic stenosis [31], again suggesting a causal relationship between renalase and cardiac hypertrophy. The authors postulated the potential link knowing that in hypoxia, glycolysis is increased and that renalase is secreted in the manner of preserving primary metabolism [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cardioprotection, renalase was validated to inhibit the profibrotic gene expression and phosphorylation of the extracellular signal–regulated kinase 1/2 pathway, therefore preventing adverse cardiac remodeling ( 5 ). Furthermore, a hypoxic environment moves the mitochondrial oxidative metabolism toward glucose uptake, resulting in increased glycolysis; therefore, renalase may be secreted in the process of preserving the primary metabolism ( 8 ). Coupled with this, higher levels of renalase were previously confirmed in unstable angina pectoris patients, presuming that renalase rises in such conditions, owing to the body's metabolic changes, postponing its elevation grants mitigation of emergency cardiovascular conditions, including CAD ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma renalase concentration is most likely up-regulated by circulating catecholamine levels, aiming to metabolize them (3)(4)(5) and significantly improving impaired hemodynamic in vivo (3). The most recent research has implicated renalase in numerous cardiovascular pathologies: HF (6, 7), coronary artery disease (CAD), hypertension, diabetes mellitus, and aortic stenosis (8)(9)(10)(11)(12)(13)(14)(15). Moreover, substantial evidence showed that functional polymorphisms of the renalase gene were associated with cardiac hypertrophy in patients with aortic stenosis (8) and an increased risk of CAD in the general population (9) and in hemodialyzed patients (10), patients with hypertension and associated CAD (11), patients with unstable angina pectoris and concomitant metabolic syndrome (12), and in patients with stable CAD, presenting with cardiac hypertrophy, ventricular dysfunction, and inducible ischemia (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation